DETERMINING OF FORMATION WATER SATURATION TO ESTIMATE REMINING HYDROCARBON SATURATION IN THE X LAYER Y FIELD - Ratnayu Sitaresmi; Guntur Herlambang Wijanarko; Puri Wijayanti; Danaparamita Kusumawardhani (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
Efforts are made to find the remaining hydrocarbons in the reservoir, requiring several methods to calculate the parameters of reservoir rock characteristics. For this reason, logging and core data are required. The purpose of this research is to estimate the Remaining Hydrocarbon Saturation that can be obtained from log data and core data. With several methods used, can determine petrophysical parameters such as rock resistivity, shale volume, effective porosity, formation water resistivity, mudfiltrate resistivity and rock resistivity in the flushed zone (Rxo) and rock resistivity in the Uninvaded Zone which will then be used to calculate the Water Saturation value Formation (Sw) and Mudfiltrat Saturation. (Sxo) In this study four exploratory wells were analyzed. Shale volume is calculated using data from Gamma Ray Log while effective Porosity is corrected for shale volume. Rw value obtained from the Pickett Plot Method is 0.5 μm. The average water saturation by Simandoux Method were 33.6%, 43.4%, 67.0% and 39.7% respectively in GW-1, GW-2, GW-3 and GW-4 wells. While the average water saturation value by the Indonesian Method were 43.9%, 48.8%, 72.3% and 44% respectively in GW-1, GW-2, GW-3 and GW-4 wells. From comparison with Sw Core, the Simandoux Method looks more appropriate. Average mudfiltrate (Sxo) saturation by Simandoux Method were 65.5%, 68.2%, 77.0% and 64.6% respectively in GW-1, GW-2, GW-3 and GW wells -4. Remaining Hydrocarbon Saturation (Shr) was obtained by 34.5%, 31.8, 23%, 35.4% of the results of parameters measured in the flushed zone namely Rxo, Rmf and Sxo data. For the price of Moving Hydrocarbons Saturation or production (Shm) is 31.9%, 24.8%, 10%, 24.9% in wells GW-1, GW-2, GW-3 and GW-4.